Money Laundering Practices and Singapore’s Steps Against Indonesian Tax Amnesty - Prakoso, Septyanto Galan; Wibowo, Royce Kharisma Agung; Ardita, Nadia Dian; Putra, Ferdian Ahya Al; Puspitasari, Retnaningtyas (Jurnal Ilmiah Hubungan Internasional, 2024)
Singapore is a country that implements a foreign direct investment policy to advance its economy. The implementation of those policies is classified as a two-pronged sword because it also ensures the privacy and security of corrupt money investments from other countries. Because of this, many Indonesian citizens are involved in money laundering through investments in Singapore. There were cases of money laundering with the value reaching at least Rp 9,427 trillion Indonesian money in Singapore in 2016 alone. The question is why Singapore tried to mute and undermine Indonesian tax amnesty? The purpose of this paper is to find the causes of the problem. Theory and the concept that will be used by the writer are Foreign Direct Investment Theory by David K. Eitemen and Money Laundering Concept itself. This paper uses an explanative qualitative method, and a literature study to obtain the data to strengthen this paper. Based on the case and the problem, the author concluded that the economy of Singapore will be threatened by the Indonesian Tax Amnesty policy, although not majorly, considering that even though they are a country of investment, they have a strong economy, to begin with.